Utilizing PhET Simulator in Guided Inquiry Learning to Enhance Students Motivation and Science Learning Outcomes - Ni Kadek Ratna Pratiwi; A. A. Istri Agung Rai Sudiatmika; Ni Made Pujani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the differences in motivation and science learning outcomes between students who use the guided inquiry learning model assisted by PhET Simulation media and those who use conventional learning models. This research is a quasi-experimental study with a non-equivalent pretest-posttest control group design. The research population consisted of all eighth-grade students at SMP Negeri 4 Petang in the 2023/2024 academic year, totaling 75 students from three classes. Two classes (50 students) were selected as samples using a random sampling technique. Learning motivation data were collected through questionnaires, while learning outcome data were obtained through tests. The data were analyzed using descriptive statistical techniques and MANOVA analysis. The results showed: (1) there was a significant difference in learning motivation between students who used the guided inquiry model assisted by PhET Simulations and those who did not (p=0.006<0.05), (2) there was a significant difference in learning outcomes between the two groups (p=0.000<0.05), and (3) simultaneously, there were significant differences in both motivation and learning outcomes between students who used and did not use the PhET-assisted guided inquiry model (p=0.000<0.05).